"Submerges … Coming out Again and Then Flowing": What Historical Documents Tell Us About the Character of the Santa Cruz River. Issue 3 (2nd July 2020) - Seymour, Deni J.
Abstract : The Santa Cruz River, like all the major rivers in southeastern Arizona and the region, had a permanent year-round flow that was restricted to limited segments of the river. This is where the Sobaipuri O'odham established their villages because the reliable surface flow allowed them to farm with irrigation canals. Early historical period observations indicate that the Santa Cruz and other regional rivers were characterized by patchworks of pasturelands, agricultural fields and canals, shady groves of mature trees, marshes, and expanses of dry sand, in contrast to the many previously suggested reconstructions. The underlying fundamentals of the river valley have been determined by surface water availability and although periodically transformed by floods, downcutting, drought, and human factors the riparian corridor has regenerated.